Perancangan Rumah Sakit Jiwa Kelas B di kota Medan Dengan Tema Arsitektur Perilaku - Qadri, Syarifuddin; Barky, Neneng Yulia; Rambe, Yunita Syafitri (Universitas Medan Area, 2024)
This study aims to analyze the design of Mental Hospitals with appropriate facilities to support the healing of patients with mental disorders, especially schizophrenia. This study uses primary data from field surveys and secondary data from literature. Location selection is based on criteria of spatial planning, accessibility, and environmental conditions, with planning, site, and design analysis. The descriptive method ensures that the design supports the patient's recovery in a holistic manner as well as socially and technically relevant. The results of the study show that this study designed a Class B Mental Hospital in Medan Petisah, a strategic location in the trade and health center of Medan City, with an area of ±20,000 m². The design concept includes the management of sun, rain, wind, and vegetation to create a comfortable and healthy environment. Noise handling is carried out through strategic building placement and damping elements. The circulation system of people and vehicles is designed to be safe and efficient, with adequate parking space. The building uses a reinforced concrete structure with clear functional zones to support activities.